The Effect of Jigsaw Cooperative Learning Model on Students' Ability to Understand Fable Texts in Fourth Grade - Hati Harahap, Murni; Sutikno; Rahmat Kartolo (International Journal of Educational Research Excellence, 2026)
This study was motivated by the low ability of fourth-grade students at UPT SD Negeri 064956 Medan to understand fable texts. Preliminary observations indicated that most students struggled to analyze the intrinsic elements of fables, showed low levels of participation and enthusiasm in learning, and were subject to predominantly lecture-based instruction, which failed to capture their interest. These conditions revealed a gap between the learning objectives and students' actual achievements, highlighting the need for innovation in the learning model. The population and sample comprised all 28 fourth-grade students of UPT SD Negeri 064956 Medan. Data were collected through fable comprehension tests (pre-test and post-test), observations, interviews, and questionnaires. The results showed a significant improvement in students’ ability to understand fable texts after the implementation of the Jigsaw model. In Phase 1 (before the Jigsaw model was applied), the average comprehension score was 63. Of the 28 students, 18 (64.3%) had not yet met the Minimum Mastery Criteria (KKM) of 75, and only 10 students (35.7%) were in the “good” category (scores between 75–84). After applying the Jigsaw cooperative learning model in Phase 2, the average student score increased sharply to 88. All 28 students (100%) achieved scores within the “very good” category (85–100), successfully exceeding the KKM. This increase from an average of 63 to 88 strongly indicates that the Jigsaw cooperative learning model is effective in enhancing students’ comprehension of fable texts. This success is attributed to the characteristics of the Jigsaw model, which promote active participation, collaboration within expert groups, and individual responsibility in sharing knowledge. Questionnaires and interview responses also reflected positive feedback from both students and teachers, indicating that the model made the learning process more enjoyable, easier to understand, and helped develop students’ discussion skills and self-confidence